Gold as a store of value - Harmston, Stephen; World Gold Council (London : Centre for Public Policy Studies, 1998)
The first chapter considers the very long-term purchasing power (rate of exchange with other commodities and intermediate products) of gold in the US (1796-1997), Britain (1596-1997), France (1820-1997), Germany (1873-1997) and Japan (1880-1997). The second chapter investigates the recent gold price in relation to historic levels, and the fundamental supply and demand conditions for gold, to establish the extent to which the abolition of convertibility of the dollar in 1971 led to a sea-change in the determinants of the value of gold.
ne 4/04/2018
Loans
Keywords: Gold